High Frequency Burst Firing of Granule Cells Ensures Transmission at the Parallel Fiber to Purkinje Cell Synapse at the Cost of Temporal Coding - van Beugen, Boeke J.; Gao, Zhenyu; Boele, Henk-Jan; Hoebeek, Freek; De Zeeuw, Chris I. (Frontiers in Neural Circuits, 2013)
Cerebellar granule cells (GrCs) convey information from mossy fibers (MFs) to Purkinje cells (PCs) via their parallel fibers (PFs). MF to GrC signaling allows transmission of frequencies up to 1 kHz and GrCs themselves can also fire bursts of action potentials with instantaneous frequencies up to 1 kHz. So far, in the scientific literature no evidence has been shown that these high-frequency bursts also exist in awake, behaving animals. More so, it remains to be shown whether such high-frequency bursts can transmit temporally coded information from MFs to PCs and/or whether these patterns of activity contribute to the spatiotemporal filtering properties of the granule cell layer. Here, we show that, upon sensory stimulation both in un-anesthetized rabbits and mice, GrCs can show bursts that consist of tens of spikes at instantaneous frequencies over 800 Hz. In vitro recordings from individual GrC-PC pairs following high-frequency stimulation revealed an overall low initial release probability of ~0.17. Nevertheless, high-frequency burst activity induced a short-lived facilitation to ensure signaling within the first few spikes, which was rapidly followed by a reduction in transmitter release to prevent immediate postsynaptic saturation. The facilitation rate among individual GrC-PC pairs was heterogeneously distributed and could be classified as either ‘reluctant’ or ‘responsive’ according to their release characteristics. Despite the variety of efficacy at individual connections, grouped activity in GrCs resulted in a linear relationship between PC response and PF burst duration at frequencies up to 300 Hz allowing rate coding to persist at the network level. Together, these findings support the hypothesis that the cerebellar granular layer acts as a spatiotemporal filter between MF input and PC output (D’Angelo and De Zeeuw, 2009).